MODELOS DE AÇÕES SOLIDÁRIAS: UM EXAME MULTICASO - Corrêa, Leonor (2007)
This work, seeking to understand how this process occurs, called "Community Development" (SOUZA, 1991), realizing it is his historical process, as well as its contemporary, which include collective and social attributes, favorable to the understanding and application of concepts the solidarity, which are part of this social category economical. For this, proposing a dialogue between the theoretical benchmark addressed in this work, with the reports of "Stories of Lives", developed in the field of research, providing a reading practice solidarity, which can arouse a new sense the community by means cultural and collective participation. The method of search, used was the "Qualitative" in character "Exploratory", and analysis of the data raised, if proceeded with inspiration "Phenomenological." The technique was used to search the experiential, through the approach of "stories of life", to understand how the subject of search, represented by Eye Live Cooperative de Confections and Doctors, in the city of Santo André and the Association for the Promotion and Human Rescue of Citizenship Father Leo Commissary, in the city of Sao Bernardo do Campo, in Sao Paulo, understand the concept of economic solidarity, and what the existence of the practice solidarity, which facilitate, or interfere promote the generation of employment and income, within these communities. The analysis of the reports of life, these subjects of search, showed that the practice of solidarity among residents occurs only in situations of extreme need for survival, but specifically in the community of Sacadura Cabral. See that this mutual aid within this community, occurs on a voluntary basis, disaggregated understanding of the term solidarity. The social responsibility of educational institutions in the region Superior ABC Paulista encouraged the creation of the Cultural Corridor of Economic Solidarity ABC Paulista, whose commitment to the search, social responsibility and teaching practices of higher education, pointing to the need for support local communities, targeting mainly its development through instruments of empowerment, aimed at generating jobs and income.(AU)